2020
DOI: 10.1177/0022219420918840
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Reading Growth Among Students With Severe Reading Deficits Who Received Intervention to Typically Achieving Students and Students Receiving Special Education

Abstract: This study compared the reading growth of students with and without learning disabilities, and students with and without reading deficits in response to tier 2 reading interventions within a response-to-intervention framework. Participants were 499 second- and third-grade students in six urban schools. Students who scored at or below the 10th percentile on the fall reading screening assessment were identified as having a severe reading deficit and received a tier 2 reading intervention that was targeted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…Evidence exists that this early intervention and prevention framework is effective across groups of children, including BIPOC children (Robinson, 2013; Rojas, 2018). This evidence is particularly robust in early grades (Burns et al, 2020).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Evidence exists that this early intervention and prevention framework is effective across groups of children, including BIPOC children (Robinson, 2013; Rojas, 2018). This evidence is particularly robust in early grades (Burns et al, 2020).…”
mentioning
confidence: 88%
“…A meta-analysis has found that in kindergarten through third grade, MTSS can be effective and feasibly implemented (Wanzek et al, 2016). Children in second and third grades with severe reading deficits who received reading interventions grew at a rate equal to the growth rate of students without reading deficits and had growth rates significantly higher than students receiving special education services for reading (Burns et al, 2020). Although the intersection between dyslexia risk from universal screening and MTSS as an intervention model for students with elevated risk levels have limited research, greater calls from the field suggest that preventive models in school systems should be considered (e.g., Catts & Hogan, 2021; Miciak & Fletcher, 2020).…”
Section: Interventionmentioning
confidence: 99%
“…Nonetheless, there are also issues with the exclusive use of RtI for disability identification. As indicated by Burns et al (2020), low performing students who receive targeted and quality interventions demonstrate growth at more significant rates than children who are placed in special education. This success is admirable; however, the research base for interventions to improve outcomes of Black youth specifically is underexplored.…”
Section: Issues With Response-to-interventionmentioning
confidence: 99%
“…From a historic standpoint, these issues are not new, with proponents of IQ testing (see Schneider & Kaufman, 2017) maintaining that these tests are important for understanding the educational and psychological needs of students. In contrast, others have stated that implementing and monitoring interventions in general educational classrooms is the most equitable and efficient method for identifying needs and improving achievement (see Burns et al, 2020).…”
mentioning
confidence: 99%
“…Los resultados muestran cómo los estudiantes en riesgo de DEA en lectura que recibieron una intervención en el nivel 2 del modelo RtI mejoraron sustancialmente su capacidad lectora (Burns et al, 2020;. En algunos casos, se demuestra que la mejoría puede mantenerse incluso cuatro años después de la intervención (Svensson et al, 2019) o que la aplicación del RtI con niveles 2 y 3 invertidos es la más adecuada cuando lo que se persigue es la lectura del mayor número de palabras (Bouton et al, 2018).…”
Section: Modelo Rti Y Lecturaunclassified